2019
DOI: 10.12688/hrbopenres.12940.1
|View full text |Cite
|
Sign up to set email alerts
|

The C9orf72 expansion is associated with accelerated respiratory function decline in a large Amyotrophic Lateral Sclerosis cohort

Abstract: Introduction: The C9orf72 hexanucleotide repeat expansion is causal in amyotrophic lateral sclerosis (ALS) and has a negative effect on prognosis. The C9orf72 repeat expansion has been associated with an accelerated deterioration of respiratory function and survival in a cohort of 372 Portuguese patients. Methods: Cases presenting to the Irish ALS clinic with both longitudinal occluded sniff nasal inspiratory pressure (SNIP) and C9orf72 testing were including in the study. Clinical variables and survival chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Given that CSF NfL levels are reported to be higher in patients with C9orf72 mutations ( Huang et al, 2020 ) and lower in those with SOD1 mutations ( Zetterberg et al, 2007 ), this may also represent a confounding factor. Further studies are needed to clarify if genotype-specific differences exist independent of disease aggressiveness, as, for example, C9orf72 expansion carriers are known to have a worse prognosis relative to patients with sporadic ALS or other familial mutations ( Miltenberger-Miltenyi et al, 2019 ; Rooney et al, 2019 ). The presence of clinically overt FTD was assessed, but this should be examined in more detail in future studies, as previous data have indicated links between cognitive deterioration and NfL levels ( Illán-Gala et al, 2018 ; Delaby et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that CSF NfL levels are reported to be higher in patients with C9orf72 mutations ( Huang et al, 2020 ) and lower in those with SOD1 mutations ( Zetterberg et al, 2007 ), this may also represent a confounding factor. Further studies are needed to clarify if genotype-specific differences exist independent of disease aggressiveness, as, for example, C9orf72 expansion carriers are known to have a worse prognosis relative to patients with sporadic ALS or other familial mutations ( Miltenberger-Miltenyi et al, 2019 ; Rooney et al, 2019 ). The presence of clinically overt FTD was assessed, but this should be examined in more detail in future studies, as previous data have indicated links between cognitive deterioration and NfL levels ( Illán-Gala et al, 2018 ; Delaby et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The time by CR interaction term represents 33 diagnostic delay, 34 site of onset 35 and C9orf72 repeat expansion status (see table 2). 36 The longitudinal mixed model and Cox survival models were then used to create joint longitudinal and time-to-event models (joint models), using the R package JMBayes. 37 This analysis enabled the model to control for non-random drop-out in our longitudinal data, resulting in less biased effect estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, age is not particularly relevant for patient stratification [25]. The genetic related variables (i.e., familial history of ALS and C9orf72 HRE) were also found to have minimal influence on all progressing groups, despite the association between C9orf72 HRE and accelerated respiratory function decline [26,27]. The time‐independent clinical variables gender, El Escorial criteria at diagnosis and region of onset have residual influence.…”
Section: Discussionmentioning
confidence: 99%